'Quasi‐Mixture' Descriptors for QSPR Analysis of Molecular Macroscopic Properties. The Critical Properties of Organic Compounds. Issue 10 (2nd September 2014) - Mokshyna, E.; Nedostup, V. I.; Polishchuk, P. G.; Kuzmin, V. E.
Abstract Rational approach towards the QSAR/QSPR modeling requires the descriptors to be computationally efficient, yet physically and chemically meaningful. On the basis of existing simplex representation of molecular structure (SiRMS) the novel 'quasi‐mixture' descriptors were developed in order to accomplish the goal of characterization molecules on 2D level (i.e. without explicit generation of 3D structure and exhaustive conformational search) with account for potential intermolecular interactions. The critical properties of organic compounds were chosen as target properties for the estimation of descriptors' efficacy because of their well‐known physical nature, rigorously estimated experimental errors and large quantity of experimental data. Among described properties are critical temperature, pressure and volume. Obtained models have high statistical characteristics, therefore showing the efficacy of suggested 'quasi‐mixture' approach. Moreover, 'quasi‐mixture' approach, as a branch of the SiRMS, allows to interpret results in terms of simple basic molecular properties. The obtained picture of influences corresponds to the accepted theoretical views.